Predicting the Maximum Dynamic Deflection of Rigid Pavement Slab at Toll Road Due to Vehicle Load - Haripriambodo, Tjatur; Alisjahbana, Sofia W.; Najid, Najid; Widjajakusuma, Jack (Jurnal Locus Penelitian dan Pengabdian, 2025)
Several points on Indonesia Toll Road found cracks in the concrete slab very early, not long after the road was operated, especially on toll roads with large volumes of vehicles (trucks) transporting materials and industrial products. The most common failure modes that occur in rigid pavements are fatigue cracks in the concrete slab and/or erosion of the material in the subbase. Both are related to excessive stress and deflections in the concrete slab. Currently, vehicular loading is commonly modelled as static load in concrete design guidelines although it has a dynamic nature. However, dynamic analysis of concrete pavements has been attracting researcher’s attention. The American Association of State Highway and Transportation Officials (AASHTO) conducted an experimental test of concrete pavements to determine effect of vehicle velocity from 3.2 km/h to 95.6 km/h by using different single truck vehicles. The AASHTO result showed that increased vehicle speed from 3.2 km/h to 95.6 km/h decreased pavement responses by about 29%. This research was intended to predict dynamic deflection through implementation Pasternak – Vlasof foundation model and primary data. Deflection was successfully calculated through numerical analysis by taking finite element method. Result was obtained maximum deflection that happened at 2 km/hour vehicle speed. Attention was also paid to 40 km/hour vehicle speed which produces relatively higher deflection than others.